(3Gdefgd GdMOjK aj TQM GdMOjK (B/s - (3dGTjf, ehSi TGgjf,s 1920-2009; (3YHO GdYGd, YHO GdYGd CMeOs; (3GdHNGQj, eMeO Hf ESeGYjd Hf EHQGgje,s 194-256 (3g`(B.s ((3GdbGgQI (B:s (3OGQ GdJQGK GdYQHj,s)
(3TQM CMGOjK eNJGQI ef UMjM GdHNGQj(B.s
Keywords: (3GdMOjKs -- (3TQMs; (3GdMOjKs -- (3GdeSGfjOs; (3GdMOjKs -- (3UMjM GdHNGQjs